Use of Instagram as learning media in senior high school - Muhammad Nur Iman Hadiyana Setia; Monica Fajriana (Universitas Pendidikan Indonesia, 2022)
This study examines using Instagram as an innovative learning tool for high school students. The indicators assessed are the easiness, frequency, and experience that Instagram provides as a learning tool. This study used a qualitative approach and collected data using a questionnaire completed by SMA/SMK/MA/MAK students. The study used a Likert scale by giving weight to each available answer. The weights in each category will be summed and converted into qualitative data. The data will be drawn by counting how many categories of answers from all respondents. The results showed that forty-four point four percent of students who were respondents agreed with Instagram as a learning tool. The results showed that respondents considered Instagram an easy-to-use learning tool. Instagram's position is ideal as a learning tool because students are comfortable using it. Teachers are expected to use Instagram social media more often as a learning tool so that the benefits of using Instagram can be more optimized in supporting student learning achievements Abstrak Penelitian ini bertujuan untuk meneliti efektivitas penggunaan Instagram sebagai inovasi media pembelajaran untuk peserta didik Sekolah Menengah Atas. Indikator yang dinilai adalah kemudahan, frekuensi, dan pengalaman yang diberikan Instagram sebagai media pembelajaran. Penelitian ini menggunakan metode pendekatan kuantitatif dan mengumpulkan data dilakukan menggunakan kuesioner yang diisi oleh peserta didik SMA/SMK/MA/MAK. Penelitian menggunakan skala Likert dengan memberi bobot pada setiap jawaban yang tersedia. Hasil penelitian menunjukkan bahwa peserta didik yang menjadi responden setuju apabila Instagram sebagai media pembelajaran. Berdasarkan hasil penelitian, responden menganggap Instagram adalah media pembelajaran yang mudah digunakan. Kedudukan Instagram ideal untuk sebuah media pembelajaran, karena peserta didik sebagai pengguna tidak merasakan kesulitan saat menggunakannya. Untuk menjadikan Instagram sebagai media pembelajaran yang efektif terdapat beberapa tantangan yang perlu dihadapi berkaitan dengan kepercayaan diri peserta didik, motivasi dalam membuat konten, serta materi pada konten itu sendiri. Kata Kunci: Instagram; inovasi pembelajaran; media pembelajaran; media sosial